O político nas leis nacionais de educação - Sepel, Franciele Farias (2019)
In the current Brazilian educational scenario, considering the second decade of the 21st century not finished yet, a proposal to change educational laws becomes controversial: the attempt to insert the “Projeto de Lei Escola sem Partido” (PLESP) in law of Diretrizes e Bases da Educação (LDB). The PLESP in its positions, has inspired the proposition of several other projects that intend to dispense with the teacher's pedagogical practice, aiming to avoid an alleged ideological and political "indoctrination" in the classroom. This proposal is widely questioned because, among other issues, it indicates that every classroom should have a poster, which contains new guidelines for the teacher, which, in turn, aim to determine how the teacher should behave and including what you can say or what you need to silence, being liable to punishment if/when considered a offender. This project, given its character, is being discussed, either by supporters or critics, at the same time as it is being presented in several instances, namely: at the national level, the Senado Federal and the Congresso Nacional; at the state level in at least seventeen Assembléias Legislativas of federative units; at the municipal level, in eighty-five city councils of Brazilian municipalities. In this paper, therefore, we aim to reflect on this issue, taking as discursive materialities for analysis, discursive clippings of the vídeo “Roda Viva | Leandro Karnal, 04/07/2016”, of article “UFPR diz que „Escola sem Partido‟ limita ensino e pode gerar perseguições” by Rogério Galindo and the vídeo “Prof. Fernando Penna - Audiência Pública sobre “Escola sem Partido” (Senado Federal 16/11/2016)” and some of their comments in the digital scope. The theoretical support to be used will be the concepts of French Line Discourse Analysis (AD), added to the concepts of “politics” and “political” from Aristóteles, Hannah Arendt and Jacques Rancière as well as “Left and “Right” by Joelza Ester Domingues e Bertoni de Oliveira Sousa. Also, in this paper we try to observe possible impacts on Education and on Brazilian society as a whole if the implementation of Projeto de Escola sem Partido occurs and also to interpretation of the PLESP based on what was said by the authors of the elected corpus.